2007
DOI: 10.4103/0970-1591.36719
|View full text |Cite
|
Sign up to set email alerts
|

A review of urodynamic evaluation in children and its role in the management of boys with posterior urethral valves

Abstract: Posterior urethral valves are the commonest cause of lower urinary tract outflow obstruction in male infants with an estimated incidence of 1:5000 male infants and 1:25,000 live births. Despite treatment with fulguration of the obstructing valves, bladder function is abnormal in up to 70% of older children and adolescents. Bladder dysfunction causes morbidity e.g. urinary incontinence and has been implicated in the late deterioration of renal function in this population. A poor understanding and inappropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
(13 reference statements)
1
11
0
Order By: Relevance
“…Posterior urethral valves (PUV) are the most common cause of congenital lower urinary tract outflow obstruction in male infants with an incidence of 1:5,000 male infants and 1:25,000 live births. [ 1 2 3 ] The incidence is unknown in our sub-region. Uba et al [ 1 ] in Jos, Nigeria reported 3–8 cases per annum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior urethral valves (PUV) are the most common cause of congenital lower urinary tract outflow obstruction in male infants with an incidence of 1:5,000 male infants and 1:25,000 live births. [ 1 2 3 ] The incidence is unknown in our sub-region. Uba et al [ 1 ] in Jos, Nigeria reported 3–8 cases per annum.…”
Section: Introductionmentioning
confidence: 99%
“…The anomaly is associated with considerable morbidity including urosepsis, urinary incontinence (over-flow), chronic renal insufficiency (RI), and even death. [ 2 6 ] Odetunde et al [ 5 ] In Enugu, Nigeria reported that the bulk of patients seen with PUV in their practice presented late with urosepsis, anemia, uremia, and ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior urethral valve (PUV) is the most common lower urinary tract congenital anomaly in boys with an incidence of 1: 5000–1:8000 males [ 1 5 ]. It is the leading cause of bladder outlet obstruction and renal insufficiency in male children [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result from persistent and unrelieved pressure on the bladder leading to bladder diverticular, hydronephrosis and chronic to end-stage renal diseases (ESRD). The anomaly is associated with high mortality and morbidity including urosepsis, overflow urinary incontinence, chronic kidney diseases (CKD), hypertension, chronic anaemia, failure to thrive, poor quality of life and even death [ 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…(3) inherent renal dysplasia; and acquired problems including (4) progressive vesical dysfunction, (5) megaureter with progressive renal scarring, and (6) metabolic and systemic complications [11][12][13].…”
Section: Hypothesis Regarding the Possible Embryological Basis Of Sevmentioning
confidence: 99%